Cooperative Script Management in Improving Students' Intensive Reading Skills - Deni Gunawan; Helmawati Helmawati (Journal of Innovation and Research in Primary Education, 2026)
Indonesian elementary students' reading literacy remains critically low, with 2018 PISA results ranking Indonesia 74th among 79 countries. This study examines Cooperative Script management in improving fourth-grade students' intensive reading skills, addressing the knowledge gap regarding how planning, organizing, implementing, and evaluating cooperative learning are managed across diverse resource contexts. A qualitative multiple case study was conducted at SDN Bungasari and SDN Wanasari, Cianjur Regency, over six months. Data were collected through semi-structured interviews with principals, teachers, and students; systematic classroom observations; and document analysis. Analysis employed Miles, Huberman, and Saldaña's interactive model using Terry's POAC framework. Findings reveal that systematic Cooperative Script management significantly improved students' intensive reading skills, including main idea identification, text summarization, and critical thinking, while enhancing confidence, motivation, and communication abilities. Both schools achieved substantial gains despite contrasting teacher resource availability through adaptive planning, strategic heterogeneous pairing, and context-appropriate implementation strategies. Time constraints and supervision challenges were successfully mitigated through structured scheduling, peer tutoring, and scaffolding worksheets. Results align with constructivist learning theories and demonstrate that management quality mediates instructional effectiveness. The study extends Cooperative Script literature by establishing educational management as a critical variable determining implementation success, offering evidence-based guidance for teachers, administrators, and policymakers in resource-constrained contexts.